Highly efficient photocatalytic degradation of Reactive Black 5 using Ti-based mixed oxide nanocomposites - Lee, Fui San; Teo, Siow Hwa; Joseph, Collin Glen; Ng, Chi Huey; Zhang, Putao; Shamsuddin, Mohd Razali; Taufiq-Yap, Yun Hin; Alsultan, Abdulkareem Ghassan; Lim, Hong Ngee; Ibrahim, Izwaharyanie; Moh, Pak Yan (Springer Nature, 2026)
Bulk titanium dioxide (TiO2) has been actively used in wastewater treatment to remove organic compounds. However, it suffers from low utilization of the light spectrum and rapid charge recombination. In this work, a binary oxide nanocomposite (CdO/TiO2), also denoted as CT was employed to overcome the limitations of bulk TiO2 in reactive black 5 (RB-5) degradation. The CdO/TiO2 nanocomposite was prepared through a facile sol–gel method. The intact adhering of CdO on the TiO2 surface has substantially enhanced the CT’s bandgap alignment, consequently enhancing the light absorption ability of CT up to the visible region. The doping of CdO onto the TiO2 induces smooth transportation of photogenerated charge carriers, thus suppressing undesirable charge recombination. Consequently, a 3.3-fold increment (94.49%) of RB-5 degradation performance was observed compared to the pristine TiO2. CdO/TiO2 could be used as a catalyst for at least four cycles without significant change to the crystallinity and catalytic activity.